Pengembangan Buku Ajar Biologi Topik Ekologi Kelas Vii SMP Berbasis Penemuan Terbimbing dengan Memanfaatkan Lingkungan Kebun Sayur - Depari, Tresia Valentina; Manurung, Binari; Sudibyo, Mufti (Magister Pendidikan Biologi, Universitas Negeri Medan, 2016)
This study aim to generate a decent textbook to use, easy to learn and can be used for leaners individual learning which produce teaching materials based on guided discovery. This research is the development of a research model product development Borg and Gall combined with a model of Dick and Carey instructional design. The research method consisted of: (1) validation of subject matter experts; (2) validation of expert instructional design; (3) validation of biology teacher; (4) individual trial; (5) small group testing; (6) limited field trials. Test subjects consisted of two subject matter experts biology, one expert instructional design, three students for individual trials, nine students to test small group and 38 students to a limited field test. Value about the quality of the product development is collected by questionnaire and analyzed with quantitative analysis techniques descriptive. The result showed: (1) subject matter experts are very well qualifications (90,14%); (2) test of instructional design experts are very well qualifications (88,06%); (3) biology teachers are in very well qualifications (93%); (4) individual trials are in well qualifications (91,07%); (5) small group trials are in very well qualifications (90,67%); (6) limited group trial in very good qualifications (87,55%).